Efeito da vitamina D sobre o equilíbrio postural em mulheres na pós-menopausa - Oliveira, Luciana Mendes Cangussu [UNESP] (2014)
Objective: to evaluate the effect of isolated vitamin D (VitD) supplementation on the rate of falls and the postural balance in fallers postmenopausal women. Methods: In this double-blind placebo controlled trial 160 women with age 50-65 years, amenorrhea ≥ 12 months and history of falls were included. Participants were allocated at random to receive either 1,000UI VitD /day orally (n = 80) or placebo (n = 80). The intervention time was 9 months, with assessments at initial and final moments. Postural balance was assessed by stabilometry (computerized force platform). Muscle mass was estimated by Total-body DEXA and muscle strength by handgrip strength and chair-rising test. Serum levels of 25-hydroxyvitamin D [25(OH)D] were measured by HPLC. Data were analyzed according to intention-to-treat, using ANOVA, chi-square and logistic regression. Results: After 9 months, mean 25(OH)D levels increased from 15.0±7.5 ng/ml to 27.5±10.4 ng/ml (+45.4%) in the VitD group whereas decreased from 16.9±6.7 ng/ml to 13.8±6.0 ng/ml (-18.5%) in the placebo group (p<.001). The rate of fall was higher in the placebo (+46.3%, p<.001), that presented an adjusted risk of 1.9 (CI 95% 1.23-3.08) times higher of falls and 2.80 (CI 95% 1.43-5.50) times higher of recurrent falls than the VitD group. There was reduction in body sway by stabilometry, with lower amplitude of anteroposterior (-35.5%) and laterolateral (-37.0%) oscillation, only in the VitD group (p<.001). In this group, there was significant increased in muscle strength of the lower limbs by chair-rising test (+45.5%, p=0.036). Women in the placebo group presented significant reduction in the muscle mass (-5.8%) (p=0.030). Conclusion: Fallers postmenopausal women with isolated vitamin D supplementation had a lower rate of falls and improvement in postural balance and muscle strength